2022
DOI: 10.3389/fphar.2022.806682
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced Upregulation of lncRNA ELFN1-AS1 Promotes Colon Cancer Growth and Metastasis Through Targeting TRIM14 via Sponging miR-191-5p

Abstract: Hypoxia is identified as one of the microenvironmental features of most solid tumors and is involved in tumor progression. In the present research, we demonstrate that lncRNA extracellular leucine rich repeat and fibronectin type III domain-containing 1-antisense RNA 1 (ELFN1-AS1) is upregulated by hypoxia in colon cancer cells. Knockdown of ELFN1-AS1 in hypoxic colon cancer cells can reduce cell proliferation and restore the invasion to non-hypoxic levels. Fluorescence in situ hybridization results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…We found that CD4+ T cells, CD8+ T cells, NK cells, M1 macrophages, M2 macrophages, myeloid dendritic cells, and fibroblasts were more abundant in the high-risk group. Significantly, high lymphocytic infiltration in um is associated with poor prognosis, in agreement with our results [ 23 29 ]. We also found that the expression of most ICIs-related molecules and the scores of most immune functions were higher in the high-risk group than low-risk group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that CD4+ T cells, CD8+ T cells, NK cells, M1 macrophages, M2 macrophages, myeloid dendritic cells, and fibroblasts were more abundant in the high-risk group. Significantly, high lymphocytic infiltration in um is associated with poor prognosis, in agreement with our results [ 23 29 ]. We also found that the expression of most ICIs-related molecules and the scores of most immune functions were higher in the high-risk group than low-risk group.…”
Section: Discussionsupporting
confidence: 93%
“…en, 409 irlncRNAs were associated with prognosis, 6 candidate irlncRNAs (ELFN1-AS1, AF131216.4, AP005121.1, AC079089.1, AC104117.3, and SOX1-OT) were filtered out by LASSO, and 3 prognostic irlncRNAs were applied to construct a model. Among these 6 candidate irlncRNAs, ELFN1-AS1 was considered as an oncogene in a variety of cancers, AC079089.1, AC104117.3, and SOX1-OT have been shown to have a function in the progression of various diseases, and other lncRNAs were first identified [23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to DAPK1, miR-191-5p has been found to target oxidative stress responsive 1 (OXSR1), 57 special AT-rich binding protein 1 (SATB1), 58 CCAAT-box/enhancer binding protein β (C/EBPβ), 59 mitogen-activated protein kinase kinase kinase 12 (Map3k12), 60 and tripartite motif-containing 14 (TRIM14). 61 These targets have similar sequences that bind to the short seed sequences at the 5′ ends (nucleotides 2−8) of miR-191-5p. Nevertheless, the regulatory roles of miR-191-5p through its downstream targets in AD remain to be further investigated and are worthy of more in-depth exploration in future studies.…”
Section: ■ Discussionmentioning
confidence: 99%
“…ROS can upregulate TRIM37 during HBV (Hepatitis B)-associated hepatic fibrosis which is a high risk factor for hepatocellular carcinoma [ 108 ]. Under a hypoxic conditions, TRIM14 was induced by sponging miR-191-5p in colon cancer cells, inhibiting apoptosis and promoting proliferation and invasion [ 109 ]. Some TRIMs may play opposite roles: TRIM4 could sensitize cells to hydrogen peroxide (H 2 O 2 ) induced cell death [ 110 ].…”
Section: The Trim Family and Cancer Pathologymentioning
confidence: 99%